O avesso de tudo o que é humano e a orquestra feiticeira - Girotto, Karlla Barreto (2023)
This dissertation proposes to question and rethink the systems that structure and sustain the foundations of a political, social, cultural, and economic project that has its historical origins in the period of the emergence of capitalism, known as modernity. This project forged a world with serious consequences for life (not only human life) with which we still deal to this day. From this system originate solid organizations that govern common life in the West, which are called public life because of their structuring around the state as a universal principle, such as governmental institutions, the churches and their doctrines, the makers and rulers of laws, and the structures that create images and circulate them, forging a system we call cultural, often mistakenly understood as a separate sphere, when in fact it consists of a certain regime of the unconscious that produces the dominant politics of subjectivation and orientation of desire, and its formations in the social field. It seeks to scrutinize how this regime, hegemonic in its sense, reiterates the established forms of power and is, itself, one of its foundations – sustaining a certain order in the world, promoting violence, and inoculating the images to which desire is subject when guiding its choices and actions. The text points out that the notion and the understanding of what is called art were created by this system, on the basis of the sequestration of life's (individual and social, not only human) own power of creation and its confinement within this restricted scope, and that to establish other lines of creation and production, distant enough to free themselves from it, is to invigorate dying processes, including (but not limited to) what we call art. If we consider art as a practice that is integral and insubordinate to this system, it can be the bearer of a healing experience from the perspective of an ethical-aesthetical-political pragmatics that, in a radical movement, can mobilize a transformation of the regime of the dominant unconscious – freeing desire from the images that structure the conditions of a life and the relationship that subjectivity establishes with it under the domination of this regime. By situating the processes of healing from the body as a material manifestation, in its humancosmic dimension – conscious and unconscious – and in its interspecific vegetal, mineral, and animal relations, it questions the aesthetic experience when it is split and dissociated from an eco/cosmopolitical practice, a central point of the dissertation and the basis of the contradictions and violences characteristic of the hetero-eurocentered white patriarchal colonial project. Thus, it also indicates that what the West has named the unconscious after psychoanalysis is, in non-white-centered cultures, the mode of production of the forms of existence in which life is shaped in its cosmic dimension; and that entering this dimension is, in itself, a counter-colonial exercise, a healing practice that generates daily processes of distancing from colonial ruins and that, in this sense, can be called micropolitics. The dissertation points to an a-parallel perspective to the concept of Western time, since such processes imply in themselves the dimensions of another, non-segmented time. The future does not belong to a segment of the present; rather, it is at any temporal point a potency that only needs to be released, returning cosmic time to the vital engendering force of existence